Generation of high oleic acid sunflower lines using gamma radiation mutagenesis and high-throughput fatty acid profiling - Rozhon, Wilfried; Ramirez, Veronica E.; Wieckhorst, Silke; Hahn, Volker; Poppenberger, Brigitte (Frontiers in Plant Science, 2023)
Sunflower (Helianthus annuus L.) is the second most important oil seed crop in Europe. The seeds are used as confection seeds and, more importantly, to generate an edible vegetable oil, which in normal varieties is rich in the polyunsaturated fatty acid linoleic acid. Linoleic acid is biosynthesized from oleic acid through activity of the oleate desaturase FATTY ACID DESATURASE 2 (FAD2), which in seeds is encoded by FAD2-1, a gene that’s present in single copy in sunflowers. Defective FAD2-1 expression enriches oleic acid, yielding the high oleic (HO) acid trait, which is of great interest in oil seed crops, since HO oil bears benefits for both food and non-food applications. Chemical mutagenesis has previously been used to generate sunflower mutants with reduced FAD2-1 expression and here it was aimed to produce further genetic material in which FAD2-1 activity is lost and the HO trait is stably expressed. For this purpose, a sunflower mutant population was created using gamma irradiation and screened for fad2-1 mutants with a newly developed HPLC-based fatty-acid profiling system that’s suitable for high-throughput analyses. With this approach fad2-1 knock-out mutants could be isolated, which stably hyper-accumulate oleic acid in concentrations of 85-90% of the total fatty acid pool. The genetic nature of these new sunflower lines was characterized and will facilitate marker development, for the rapid introgression of the trait into elite sunflower breeding material.